Chip-based quantum signature network reaches 200 km - Chenglong You; Omar S. Magaña-Loaiza (Light: Advanced Manufacturing)
A pioneering chip-based quantum digital signature (QDS) network achieves secure document signing over 200 km of fiber, leveraging integrated photonics to miniaturize transmitters and centralize measurement systems. This breakthrough paves the way for future scalable, cost-effective, and robust quantum-secure communication networks.